Extracellular‐Matrix‐Reinforced Bioinks for 3D Bioprinting Human Tissue. Issue 3 (9th December 2020) - De Santis, Martina M.; Alsafadi, Hani N.; Tas, Sinem; Bölükbas, Deniz A.; Prithiviraj, Sujeethkumar; Da Silva, Iran A. N.; Mittendorfer, Margareta; Ota, Chiharu; Stegmayr, John; Daoud, Fatima; Königshoff, Melanie; Swärd, Karl; et al.
Abstract: Recent advances in 3D bioprinting allow for generating intricate structures with dimensions relevant for human tissue, but suitable bioinks for producing translationally relevant tissue with complex geometries remain unidentified. Here, a tissue‐specific hybrid bioink is described, composed of a natural polymer, alginate, reinforced with extracellular matrix derived from decellularized tissue (rECM). rECM has rheological and gelation properties beneficial for 3D bioprinting while retaining biologically inductive properties supporting tissue maturation ex vivo and in vivo. These bioinks are shear thinning, resist cell sedimentation, improve viability of multiple cell types, and enhance mechanical stability in hydrogels derived from them. 3D printed constructs generated from rECM bioinks suppress the foreign body response, are pro‐angiogenic and support recipient‐derived de novo blood vessel formation across the entire graft thickness in a murine model of transplant immunosuppression. Their proof‐of‐principle for generating human tissue is demonstrated by 3D bioprinting human airways composed of regionally specified primary human airway epithelial progenitor and smooth muscle cells. Airway lumens remained patent with viable cells for one month in vitro with evidence of differentiation into mature epithelial cell types found in native human airways. rECM bioinks are a promising new approach for generating functional human tissue using 3D bioprinting. Abstract : A new class of microscale phase‐separated hybrid bioinks is described by combining tissue specific extracellular matrix (ECM) with alginate. This novel rECM hybrid bioink is tissue specific, cytocompatible, biocompatible, and pro‐angiogenic, and is used to bioprint human airways composed of multiple, regionally specified primary human lung cell types.